Collaborative Innovation in Agrometeorology: Coordination Strategies to Develop a Monitoring IT System for Brazil - Delphino Bambini,Martha (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2014)
This case-study article presents the results from a morphology analysis of a knowledge and information network, focusing on the coordination mechanisms employed to generate a convergent arrangement. Agritempo was the first information system to offer (in 2003) free access to a broad range of agrometeorological data comprising all the Brazilian territory, representing an important technological innovation to the agricultural sector. To study this phenomenon an analytical framework of the Techno-Economic Network (TEN) and concepts from the Innovation Sociology field was employed. Results indicate that the durability of this arrangement - from 2003 to 2014 - can be explained by the effectiveness of the coordination strategies established in the network such as: trust based relationships; institutional and individual leadership actions; contracting; software applications and shared common working procedures.